Application of AFLP molecular markers to genetic characterisation of duck (Anas platyrhyncos), turkey (Meleagris gallopavo) and helmeted guinea fowl (Numida meleagris) Veneto breeds - M. Cassandro; M. Baruchello; C. Dalvit; C. Targhetta (Italian Journal of Animal Science, 2010)
In the last decade, the conservation of local breeds and of their genetic resources has gained more and more importance (Notter, 1999). In fact, the safeguard of animal genetic variability is determinant to maintain ecosystem equilibriums but it is also essential to guarantee future economic potentials of these animal resources. Moreover, biodiversity has a great cultural value and it can be also used for scientific purposes (FAO, 1992).